Step 1: Before going to do the problem, Find the knowns and unknowns in and note it down.

Step 2: Explore the given rule

EXAMPLE: x_{n+1} = ax_n - 3

Succeeding term = a (preceding term) - 3

Step 3: By using the given rule find the required terms (x_2, x_3,x_4...etc)

NOTE: According to the given rule substitute the values to get the required

term.

EXAMPLE: For an attempt to find the x_3

x_{n+1} = ax_n - 3

x_3=ax_2-3

Substitute the values x_2 [ Calculate x_2(x_2=a-3,\ take\ x_1=1 since n>1)]

x_3 = a(a - 3) - 3

x_3 = a^2 – 3a – 3

Step 4: Compare the result with the given answer, verify is it equating or not